Of Primary Features in Aesthetics: A Critical Assessment of Generalism and a Limited Defence of Particularism. (2nd November 2018) - Tsu, Peter Shiu-Hwa
Abstract: Contemporary analytic aesthetics has seen a heated debate about whether there are general critical principles that determine the merits/demerits of an artwork. The so-called generalists say 'yes', whereas the so-called particularists say 'no'. On the particularists' view, a feature that is a merit in one artwork might well turn out to be a defect in another, so critical principles purporting to define merits and defects are pretty much in vain. Against this, the generalists argue that while some features change their status in the way suggested by the particularists not all features do; there are still some features that remain merits or defects across different contexts; these are what the generalists call 'primary features'. If so, the generalists maintain that there are still general critical principles generated by these primary features. In this article, I provide a limited defence of particularism by critically assessing three arguments for the existence of such primary features. I first argue that Beardsley's invariable and explanatory conception of primary features is too strong, such that there is no compelling reason for us to believe in their existence. I then argue that Sibley's prima facie conception and Dickie's isolation conception of primary features are both too weak—in other words, even if primary features of these kinds exist, they do not generate the sort of critical principles that the particularists reject. Finally, I argue that Connolly and Haydar's recent attempt to revive the Beardsleyan conception fails. As a result, I contend that there is reason to believe that particularism remains as a live option.